The Towers of New Capital Mega Townships in India - Tiwari, P. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Based on the study of a number of large mega township projects under development on the urban fringes of Delhi and Ahmedabad, The Towers of New Capital is an enquiry into how these 'global fixes' are leading to territorial reorganization. What are the social and economic impacts of large mega projects? How are these projects envisioned and governed? How transparent is the administrative decision making process? How are these projects marketed and to whom? This book explores the processes and challenges of land acquisition, urban design outcomes, planning processes, market assessment, construction project management and the marketing of such projects to users and investors in an emerging economy context.